Tata Laksana Nyeri pada Pasien Kritis di ICU - Ardi, Laurencia (Cermin Dunia Kedokteran, 2024)
Critically ill patients are patients in life-threatening conditions and will result in significant increment of mortality and morbidity if not given immediate medical intervention. Critically ill patients, especially those using ventilators, often experience pain. Pain can be caused by interventions or procedures in the ICU or by other unknown causes. Pain management in critically ill patients can be non-pharmacological or pharmacological.